2018
DOI: 10.1158/0008-5472.can-17-2269
|View full text |Cite
|
Sign up to set email alerts
|

Mutant IDH1 Cooperates with ATRX Loss to Drive the Alternative Lengthening of Telomere Phenotype in Glioma

Abstract: A subset of tumors use a recombination-based alternative lengthening of telomere (ALT) pathway to resolve telomeric dysfunction in the absence of TERT. Loss-of-function mutations in the chromatin remodeling factor ATRX are associated with ALT but are insufficient to drive the process. Because many ALT tumors express the mutant isocitrate dehydrogenase IDH1 R132H, including all lower grade astrocytomas and secondary glioblastoma, we examined a hypothesized role for IDH1 R132H in driving the ALT phenotype during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…Here we showed that the IDH1 R132H mutation is directly associated with a lack of ATRX expression and consequently, ALT as described previously [46]. In our sample, all tumors with ALT bear IDH1 R132H mutations and lost ATRX expression.…”
Section: Discussionsupporting
confidence: 87%
“…Here we showed that the IDH1 R132H mutation is directly associated with a lack of ATRX expression and consequently, ALT as described previously [46]. In our sample, all tumors with ALT bear IDH1 R132H mutations and lost ATRX expression.…”
Section: Discussionsupporting
confidence: 87%
“…Work by Mukherjee et al investigated these mutations in the context of human ALT gliomas and found that IDH1 R132H mutations led to a consistent downregulation of a number of proteins, two of which being the Shelterin component RAP1, and the DNA damage repair protein XRCC1. The authors show that in the absence of ATRX, loss of both RAP1 and XRCC1 leads to an increase in ALT markers (26). Downregulation of RAP1 has previously been shown to lead to an increase in telomere dysfunction by end uncapping, however a previous study showed that following TALEN knockout RAP1 loss did not in itself lead to an increase in telomere dysfunction or tSCEs (40,41).…”
Section: Alt In Gliomamentioning
confidence: 94%
“…Nevertheless, mutations in other proteins have been described in ALT that are believed to be involved in, or may lead to the development of the ALT phenotype. These include mutations in histone H3.3, SMARCAL1, and IDH1 (24)(25)(26). Additional correlated mutations may indeed exist, however due to the lack of routine testing for ALT in clinic, many ALT cancers are likely never fully characterized.…”
Section: The Mutational Landscape Of Altmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations that affect the function of ATRX have been associated with several types of cancers, including glioblastoma and pancreatic cancer [20,21] and ATRX aberrant expression has been recently proposed as a marker of poor survival in soft tissue sarcomas [8]. On the contrary, higher levels of ATRX protein have not described in human cancers.…”
Section: Atrx Expression Levels In Human Cancersmentioning
confidence: 99%